Program and target approach in the management system of scientific and technological development: features, tendencies and perspectives - Гречаник, Б. В.; Козак, А. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Practical experience of implementing methods of program targeted management of scientific and technical activities is analyzed. The basic problems of programming scientific and technological development in the national economy are pointed out. Certain recommendations for enhancing and extending the use of program-target management of scientific and technological development in Ukraine are offered.